Cancer incidence and adverse pregnancy outcome in registered nurses potentially exposed to antineoplastic drugs - Le Nhu D; Teschke Kay; Chow Yat; Lorenzi Maria; Beking Kris; Spinelli John J; Ratner Pamela A; Gallagher Richard P; Dimich-Ward Helen (BMC, 2010)
Abstract Background To determine the relationships of potential occupational exposure to antineoplastic drugs with cancer incidence and adverse pregnancy outcomes in a historical prospective cohort study of female registered nurses (RNs) from British Columbia, Canada (BC). Methods Female RNs registered with a professional regulatory body for at least one year between 1974 and 2000 formed the cohort (n = 56,213). The identifier file was linked to Canadian cancer registries. An RN offspring cohort from 1986 was created by linkages with the BC Birth and Health Status Registries. Exposure was assessed by work history in oncology or cancer agencies (method 1) and by estimating weighted duration of exposure developed from a survey of pharmacists and nursing unit administrators of all provincial hospitals and treatment centers and the work history of the nurses (method 2). Relative risks (RR) were calculated using Poisson regression for cancer incidence and odds ratios (OR) were calculated for congenital anomaly, stillbirth, low birth weight, and prematurity incidence, with 95% confidence intervals. Results In comparison with other female RNs, method 1 revealed that RNs who ever worked in a cancer center or in an oncology nursing unit had an increased risk of breast cancer (RR = 1.83; 95% CI = 1.03 - 3.23, 12 cases) and their offspring were at risk for congenital anomalies of the eye (OR = 3.46, 95% CI = 1.08 - 11.14, 3 cases). Method 2 revealed that RNs classified as having the highest weighted durations of exposure to antineoplastic drugs had an excess risk of cancer of the rectum (RR = 1.87, 95% CI = 1.07 - 3.29, 14 cases). No statistically significant increased risks of leukemia, other cancers, stillbirth, low birth weight, prematurity, or other congenital anomalies in the RNs' offspring were noted. Conclusions Female RNs having had potential exposure to antineoplastic drugs were not found to have an excess risk of leukemia, stillbirth, or congenital anomalies in their offspring, with the exception of congenital anomalies of the eye, based on only three cases; however, elevated risks of breast and rectal cancer were observed.